Review of Islamic Law on the Practice of Early Marriage in Limpakuwus Village, Sumbang, Banyumas - Aji, Imam Purnomo (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2024)
Early marriage is still a problem in Limpakuwus Village, Sumbang, Banyumas, especially with 9 couples out of a total of 38 who are married. This village has a belief that getting married before the age of 20 is considered taboo or "ora ilok" by the local community. Field research was conducted to understand the practice of early marriage in this village. This research method involves qualitative descriptive analysis with data collection through interviews and documentation. Primary data is in the form of direct interviews, supported by secondary data from books, journals, theses, texts and articles. The factors that encourage early marriage in this village are low education, beliefs/traditions, self-will, and pregnancy outside of marriage. Of the nine couples, belief or tradition factors dominate. Even though according to Islamic and positive law early marriage is recognized as legal, this practice in Limpakuwus Village, Sumbang, Banyumas is considered legal because it is in accordance with Islamic law and has a marriage dispensation in accordance with Indonesian laws and regulations.